Polynomial approach for the most general linear Fredholm integrodifferential-difference equations using Taylor matrix method - Mehmet Sezer; Mustafa Gülsu (International Journal of Mathematics and Mathematical Sciences)
A Taylor matrix method is developed to find an approximate solution of the most general linear Fredholm integrodifferential-difference equations with variable coefficients under the mixed conditions in terms of Taylor polynomials. This method transforms the given general linear Fredholm integrodifferential-difference equations and the mixed conditions to matrix equations with unknown Taylor coefficients. By means of the obtained matrix equations, the Taylor coefficients can be easily computed. Hence, the finite Taylor series approach is obtained. Also, examples are presented and the results are discussed.